Journal‐Based Learning, a new learning experience building on PBL at HKU. (12th August 2012) - Botelho, M. G.; Lo, E. C. M.; Bridges, S.; McGrath, C.; Yiu, C. K. Y.
Abstract Objective To evaluate the effectiveness of a new journal‐based learning (JBL) programme designed to equip students with skills necessary to understand dental research publications, thereby preparing them for continuing professional development. Materials and Methods A baseline evaluation of knowledge relating to key research terms was conducted on 52 final‐year BDS students. 11 weekly seminars were conducted from 8 clinical disciplines driven by a reading list of 2–5 journal articles along with a series of 'guidance' questions relating to research terms and content knowledge aspects of each paper to focus their reading and learning. Seminars were facilitated by discipline experts with supporting notes. An exit test based on research process and terminologies for the programme was conducted with 4 repeated questions from the baseline assessment. A systematic marking scheme was used and the results analysed. A focus group was run to collect feedback regarding students' views and experiences on the JBL experience. Findings Students showed significant improvements over the baseline score. The mean score rose from 3.5 to 11.5 in the repeated questions (P < 0.001). The focus group revealed that students had learnt new information about journal classification, evidence level determination, new research terms and the structure of research papers. From the first 4 years of PBL, students recognized the importance of learning from research papers since year 1. However, JBL gave them a deeper understanding of research and the development of critical appraisal skills. Implications JBL provided final‐year students the opportunity to learn significantly more about dental research, terminologies, paper structure, critical analysis and content knowledge through active‐learning small group seminars.